Mind-Body Therapies From Traditional Chinese Medicine: Evidence Map - Fogaça, Lissandra Zanovelo; Portella, Caio Fabio Schlechta; Ghelman, Ricardo; Abdala, Carmen Verônica Mendes; Schveitzer, Mariana Cabral (Frontiers in Public Health, 2021)
Background: The mind-body therapies of traditional Chinese medicine include several intervention types and combine physical poses with conscious relaxation and breathing techniques. The purpose of this Evidence Map is to describe these different interventions and report related health outcomes. Methods: This evidence map is based on the 3iE Evidence Gap Map methodology. We searched seven electronic databases (BVS, PUBMED, EMBASE, PEDro, ScienceDirect, Web of Sciences, and PschyInfo) from inception to November 2019 and included systematic reviews only. Systematic reviews were analyzed based on AMSTAR 2. We used Tableau to graphically display quality assessment, the number of reviews, outcomes, and effects. Results: The map is based on 116 systematic reviews and 44 meta-analyses. Most of the reviews were published in the last 5 years. The most researched interventions were Tai Chi and Qi Gong. The reviews presented the following quality assessment: 80 high, 43 moderate, 23 low, and 14 critically low. Every 680 distinct outcome effect was classified: 421 as potential positive; 237 as positive; 21 as inconclusive/mixed; one potential negative and none no effect. Positive effects were related to chronic diseases; mental indicators and disorders; vitality, well-being, and quality of life. Potential positive effects were related to balance, mobility, Parkinson's disease, hypertension, joint pain, cognitive performance, and sleep quality. Inconclusive/mixed-effects justify further research, especially in the following areas: Acupressure as Shiatsu and Tuiná for nausea and vomiting; Tai Chi and Qi Gong for acute diseases, prevention of stroke, stroke risk factors, and schizophrenia. Conclusions: The mind-body therapies from traditional Chinese medicine have been applied in different areas and this Evidence Map provides a visualization of valuable information for patients, professionals, and policymakers, to promote evidence-based complementary therapies.